ILLNESS PERCEPTION AND TREATMENT EXPECTATION IN PATIENTS WITH FUNCTIONAL NEUROLOGICAL SYMPTOM DISORDER AT LAHORE, PAKISTAN - Latif, Sara; Sitwat, Aisha (Journal of Pakistan Psychiatric Society, 2024)
OBJECTIVETo explore the perceived illness and treatment expectations of patients with Functional Neurological Symptom Disorder.DESIGN OF STUDYIt is a Descriptive Research Design PLACE AND DURATIONThe study was executed at Department of Psychiatry of government and private teaching hospitals of Lahore, Pakistan over a period of 12 months, from Jan 2023 to Dec 2023.METHODA total of 100 adult participants were recruited as per criteria. Demographic Information Questionnaire and Short Explanatory Model Interview (SEMI) were employed and the qualitative data generated from SEMI was converted to numerical codes and discrete categories by the method of stepwise reduction. The descriptive frequencies were then presented in the tabular format.RESULTSMajority of the participants were female, educated, students and housewives, with 1 – 6 months duration of the illness, mixed symptoms presentation, pseudo seizures and motor symptoms. The main reasons of onset of illness was mentioned as marriage related factors and familial and social factors and majority participants believe that magic can affect others. The intensity of the symptoms were perceived as ‘extreme intense’ associated with the fear about the worsening of symptoms and serious discomfort. The main difficulties due to illness was reported to be lack of interest in daily activities, and increase in problem in relationships. The patients expect proper treatment and prescription of medicines which was followed by responses that they will learn the diagnosis and will receive advice from doctors regarding their illness.CONCLUSIONThe patient’s perception towards their illness was serious and concerned and their expectations was receiving proper treatment, medications and learning the disorder and doctor’s advice.